2006
DOI: 10.1093/jxb/erj086
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the potential of the bacterial carotene desaturase CrtI to increase the β-carotene content in Golden Rice

Abstract: To increase the beta-carotene (provitamin A) content and thus the nutritional value of Golden Rice, the optimization of the enzymes employed, phytoene synthase (PSY) and the Erwinia uredovora carotene desaturase (CrtI), must be considered. CrtI was chosen for this study because this bacterial enzyme, unlike phytoene synthase, was expressed at barely detectable levels in the endosperm of the Golden Rice events investigated. The low protein amounts observed may be caused by either weak cauliflower mosaic virus 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…3A). The more pronounced phenotype reported here might be attributed to species-specific differences between tomato/tobacco and potato, or it may be the result of the codon-optimized CrtI gene used in this study (Al-Babili et al, 2006), probably leading to higher CrtI protein amounts. However, western-blot experiments were unable to reveal any CrtI protein in leaves of the expressor lines (data not shown).…”
Section: Expression Of Crtb-i Genes Induces Striking Alterations In Lmentioning
confidence: 75%
“…3A). The more pronounced phenotype reported here might be attributed to species-specific differences between tomato/tobacco and potato, or it may be the result of the codon-optimized CrtI gene used in this study (Al-Babili et al, 2006), probably leading to higher CrtI protein amounts. However, western-blot experiments were unable to reveal any CrtI protein in leaves of the expressor lines (data not shown).…”
Section: Expression Of Crtb-i Genes Induces Striking Alterations In Lmentioning
confidence: 75%
“…In one study, increased carotenoid accumulation was reported in Escherichia coli by replacing the native promoter of the chromosomal isoprenoid genes with the strong bacteriophage T5 promoter (Yuan et al 2006). In a second study (Babili et al 2006), a synthetic CrtI (carotene desaturase) gene was generated under the control of the endospermspecific glutelin B1 promoter that is important for increasing the b-carotene content in Golden Rice. Chen et al (2003) showed the promoter activity of terpenoid volatiles in Arabidopsis.…”
Section: Glandular Trichomes: Source For Essential Oil Production In mentioning
confidence: 99%
“…In 'Golden Rice' (Ye et al, 2000), for instance, the effectiveness of PSY (Paine et al, 2005), and not that of the bacterial carotene desaturase CrtI (Al-Babili et al, 2006), was decisive for increased carotenoid levels. Similarly, the overexpression of a bacterial PSY in canola (Brassica napus) seeds led to increased b-carotene Figure 1.…”
mentioning
confidence: 97%